"A pretty decent sort of bloke": Towards the quest for an Australian Jesus - Goroncy, Jason A. (HTS teologiese studies, 2019)
From many Aboriginal elders, such as Tjangika Napaltjani, Bob Williams and Djiniyini Gondarra, to painters, such as Arthur Boyd, Pro Hart and John Forrester-Clack, from historians, such as Manning Clark, and poets, such as Maureen Watson, Francis Webb and Henry Lawson, to celebrated novelists, such as Joseph Furphy, Patrick White and Tim Winton, the figure of Jesus has occupied an endearing and idiosyncratic place in the Australian imagination. It is evidence enough that ‘Australians have been anticlerical and antichurch, but rarely antiJesus’ (Piggin 2000:163). But which Jesus? In what follows, I seek to listen to what some Australians make of Jesus, and to consider some theological implications of their contributions for the enduring quest for an Australian Jesus.